Zakat Practices among Muslim Migrant Workers in Malaysia - Jarita Duasa (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
Zakat, one of the five pillars of Islam, is a religious obligation for Muslims worldwide, irrespective of their place of residence or work. This research investigates the factors influencing the likelihood of Muslim foreign workers in Malaysia to pay zakat fitr and zakat income. Data was collected via a survey conducted in the Wilayah Persekutuan area (Kuala Lumpur and Putrajaya), and analyzed using logistic regression. The study found that the propensity to pay zakat fitr is primarily influenced by the workers’ knowledge of zakat fitr and their employment sector. In contrast, the likelihood of paying zakat income is significantly determined by gender (with males being more likely), income level, knowledge of zakat income, and the motivational factors of religiosity and recognition. The study also revealed that the respondents’ willingness to pay zakat in Malaysia in the future is likely influenced by their understanding of the zakat distribution system in the country. These findings provide valuable insights for policymakers and zakat institutions in enhancing the efficiency of zakat collection and distribution. Further research is recommended to validate these findings in other contexts and among different demographic groups.============================================================================================================ABSTRAK - Praktik Zakat Pekerja Migran Muslim di Malaysia. Sebagai salah satu dari rukun Islam, zakat menjadi kewajiban bagi semua muslim dimanapun mereka tinggal dan bekerja. Penelitian ini menginvestigasi determinan yang mempengaruhi kemungkinan pekerja migran muslim di Malaysia untuk membayar zakat fitrah dan zakat penghasilan. Data penelitian dikumpulkan melalui survei terhadap sejumlah pekerja migran di Wilayah Persekutuan (Kuala Lumpur dan Putrajaya), dan dianalisis dengan regresi logistik. Kajian ini menemukan bahwa kecenderungan para pekerja migran untuk membayar zakat fitrah di Malaysia umumnya dipengaruhi oleh pengetahuan tentang zakat fitrah dan jenis pekerjaan mereka. Sebaliknya, untuk zakat penghasilan, kemungkinan mereka untuk membayar zakat di Malaysia dipengaruhi secara signifikan oleh jenis kelamin (laki-laki memiliki probabilitas lebih besar), tingkat pendapatan, pengetahuan tentang zakat penghasilan, dan faktor motivasi yang berkaitan dengan religiusitas dan rekognisi. Selain itu, juga ditemukan bahwa kesediaan responden untuk membayar zakatnya di Malaysia di masa yang akan datang cenderung dipengaruhi oleh pemahaman mereka tentang sistem pendistribusian zakat di negara ini. Temuan ini berimplikasi bagi pembuat kebijakan dan lembaga amil zakat dalam meningkatkan efisiensi pengumpulan dan pendistribusian zakat. Penelitian selanjutnya disarankan untuk memvalidasi temuan ini dalam konteks lain dengan kondisi demografis dan geografis yang berbeda.